2018
DOI: 10.1590/1981-6723.10817
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticaba skin extracts: phenolic compounds and antibacterial activity

Abstract: The phenolic compounds from various extracts of jabuticaba skin powder (JSP) were characterized in this study, and the antibacterial activity assessed. The phenolic compounds were extracted from the JSP using four methods: a) acetone extraction -1 g JSP: 10 mL 70% acetone, resting for 2 hours; b) aqueous extract -1 g JSP: 15 mL water, under agitation; c) ethanolic extract -1 g JSP: 15 mL acidified ethanol, under agitation; and d) methanolic extract -1 g JSP: 50 mL 50% methanol, under reflux. The antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In M. morganii, the MIC value presented by the extract was the same as the one presented by the positive control Ampicillin, and in P. aeruginosa, the extract presented even higher activity than this antibiotic. The potential of growth inhibition against E. coli, S. aureus, and L. monocytogenes found in this study is in agreement with the results obtained by Machado et al (2018). In what concerns the addition of jabuticaba epicarp extract to food matrices, no positive nor negative effects were verified in different types of sausages in terms of microbial characteristic (aerobic bacteria count) of the products along with storage time (Almeida et al, 2015;Baldin et al, 2016).…”
Section: Antimicrobial Activitysupporting
confidence: 91%
“…In M. morganii, the MIC value presented by the extract was the same as the one presented by the positive control Ampicillin, and in P. aeruginosa, the extract presented even higher activity than this antibiotic. The potential of growth inhibition against E. coli, S. aureus, and L. monocytogenes found in this study is in agreement with the results obtained by Machado et al (2018). In what concerns the addition of jabuticaba epicarp extract to food matrices, no positive nor negative effects were verified in different types of sausages in terms of microbial characteristic (aerobic bacteria count) of the products along with storage time (Almeida et al, 2015;Baldin et al, 2016).…”
Section: Antimicrobial Activitysupporting
confidence: 91%
“…Similarly, araçá stands out for its antioxidant potential, and is a source of vitamins and minerals [21]. The data from this study corroborate with investigations that affirm that much of the beneficial compounds are in the portion of the fruit peel [23,24].…”
Section: Evaluation Of Antioxidant Potentialsupporting
confidence: 85%
“…The phenolic compounds are the major responsible for the antioxidant activity in fruits [24]. In order for these compounds to be considered as antioxidants and to play their biological role, they must be capable of preventing, retarding or preventing self-oxidation or oxidation mediated by free radicals at low concentrations and that the product formed after the reaction is stable [25].…”
Section: Evaluation Of Phytochemical Compoundsmentioning
confidence: 99%
“…However, data in the current literature only show inhibition halos from jaboticaba extracts, and do not explore important parameters such as the quantification of antimicrobial activity, MIC and MBC values (Oliveira et al, 2018;Fidelis et al, 2020); Hacke et al (2016). In this work, the aqueous extract showed activity against all tested bacteria, mainly S. aureus and L. monocytogenes presenting the highest values of AB, MIC e MBC (Table 1).…”
Section: Resultsmentioning
confidence: 76%
“…The extract presented the higher inhibition zone against S. aureus (17.5 ± 0.4 mm). Oliveira et al (2018) found that aqueous extract of jaboticaba peels showed inhibitory zones of 7.2 mm and 10.5 mm against S. aureus and L. monocytogenes, respectively, although the extraction solvent used may imply on higher antibacterial capacity. The antibacterial activity of jaboticaba seeds was observed by Fidelis et al (2020).…”
Section: Resultsmentioning
confidence: 97%